Fiscal decentralization and electoral participation: Analyzing districts in Indonesia - Alfa Farah (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2019)
Many countries have adopted decentralization policies in order to strengthen democratic governance. Nevertheless, empirical literature on whether decentralization actually strengthens democratic governance is relatively limited when compared to empirical literature on the impact of decentralization on a wide array of fiscal or economic variables. Therefore, this paper empirically explores the effect of fiscal decentralization on democratic governance, particularly by highlighting one aspect of democratic governance, namely participation in local elections. Upon analyzing data from districts across Indonesia using the within-between specification, the empirical findings generally suggest that participation in district mayoral elections might not necessarily be driven by the increased autonomy that district have, but rather by some adverse consequences of decentralization such as capture by local elites. In addition, the analysis shows that when a district government gains fiscal power, this might not necessarily encourage electoral participation when the district's budget is mostly allocated to spending that does not benefit the public at large.
Keywords: H71; H72; H77; D72; 330; fiscal decentralization; fiscal autonomy; voter turnout; local election; the within-between specification